Mothers’ knowledge on immunization and the commitment to get their child immunized in a suburban region of Selangor, Malaysia - Makhdzir, Norafisyah; Rashid, Amira; Lee, Siew Pien; Zaini, Noor Hanita (IIUM Press, 2024)
Background: Information regarding the significance of childhood immunization must be provided to mothers to ensure that they will effectively adhere to the immunization regimens that have been prescribed for their children. Furthermore, the recent increase in parental hesitancy towards vaccinating their children may be linked to the spread of inaccurate information by groups opposed to vaccination, which misleads parents about the benefits of childhood immunization. Thus, this study aimed to assess the level of the mother's knowledge and commitment of getting their child to immunize surrounding childhood immunization to uncover gaps in understanding and potential barriers to immunization. This study focuses on primigravida mothers for their knowledge, attitudes, and practices regarding immunization. Methods: This study used a cross-sectional research design and gathered data from primigravida mothers who attended the Maternal and Child Health Clinic (MCH) in a suburban region of Selangor, Malaysia, from March to May 2018. The respondents were recruited via purposive sampling. The study included 72 respondents. Results: The results indicated that 68.1% of the respondents had good knowledge about their children's immunization, and 84.7% had a commitment to get their child immunized. The Pearson correlation analysis revealed a statistically significant and positive correlation between the level of mothers' knowledge and commitment to get their children to immunize of children immunized. The simple linear regression analysis results indicated a statistically significant association between age, access to internet information, and readiness for children's immunization, with a p-value of less than 0.05. Two themes were identified: (1) personal coping strategies with the subthemes: a) faith in God, b) reflection on family, and c) unleashing the power of self-motivation, and (2) Personal expectation with the subthemes: a) fostering attentiveness and empathy in patient care, and b) hospital management’s role. Conclusion: Nurses should actively assess and deliver health education regarding children's immunization to enrich the parents’ commitment of getting their children immunized, especially when online platforms have the potential to be a successful means for healthcare professionals to share factual to a larger target group. This will prevent mothers from relying on false or misleading information.